Lilium regale Wilson WRKY2 Regulates Chitinase Gene Expression During the Response to the Root Rot Pathogen Fusarium oxysporum - Li, Shan; Hai, Jun; Wang, Zie; Deng, Jie; Liang, Tingting; Su, Linlin; Liu, Diqiu (Frontiers in Plant Science, 2021)
Root rot, mainly caused by Fusarium oxysporum, is the most destructive disease affecting lily (Lilium spp.) production. The WRKY transcription factors (TFs) have important roles during plant immune responses. To clarify the effects of WRKY TFs on plant defense responses to pathogens, a WRKY gene (LrWRKY2) was isolated from Lilium regale Wilson, which is a wild lily species highly resistant to F. oxysporum. The expression of LrWRKY2, which encodes a nuclear protein, is induced by various hormones (methyl jasmonate, ethephon, salicylic acid and hydrogen peroxide) and by F. oxysporum infection . In this study, LrWRKY2-overexpressing transgenic tobacco plants were more resistant to F. oxysporum than the wild-type plants. Moreover, the expression levels of jasmonic acid biosynthetic pathway-related genes (NtAOC, NtAOS, NtKAT, NtPACX, NtJMT, NtOPR, and NtLOX), pathogenesis-related genes (NtCHI, NtGlu2, and NtPR-1), and antioxidant stress-related superoxide dismutase genes (NtSOD, NtCu-ZnSOD, and MnSOD) were significantly up-regulated in LrWRKY2 transgenic tobacco lines. Additionally, the transient expression of a hairpin RNA targeting LrWRKY2 increased the susceptibility of L. regale scales to F. oxysporum. Furthermore, an F. oxysporum resistance gene (LrCHI2) encoding a chitinase was isolated from L. regale. An electrophoretic mobility shift assay demonstrated that LrWRKY2 can bind to the LrCHI2 promoter containing the W-box element. Yeast one-hybrid assay results suggested that LrWRKY2 can activate LrCHI2 transcription. An examination of transgenic tobacco transformed with LrWRKY2 and the LrCHI2 promoter revealed that LrWRKY2 activates the LrCHI2 promoter. Therefore, in L. regale, LrWRKY2 is an important positive regulator that contributes to plant defense responses to F. oxysporum by modulating LrCHI2 expression.